Safety Profile of PrePex Male Circumcision Device and Client Satisfaction With Adolescent Males Aged 13–17 Years in Zimbabwe. (1st June 2016) - Tshimanga, Mafuta; Hatzold, Karin; Mugurungi, Owen; Mangwiro, Tonderayi; Ncube, Getrude; Xaba, Sinokuthemba; Chatikobo, Pesanai; Gundidza, Patricia; Samkange, Christopher; Dhlamini, Roy; Murwira, Munyaradzi; Gwinji, Gerald
Abstract : Background: The safety and efficacy of the PrePex device for voluntary medical male circumcision (VMMC) has been demonstrated in studies in Rwanda, Uganda, and Zimbabwe, leading to the conditional prequalification of the device for use in adults. Because the majority of VMMC clients in the 14 priority countries are adolescents under 18 years, research to establish the safety and efficacy of the device for males <18 years is required. Methods: One-arm, prospective study included 402 adolescents, aged 13–17 years, using PrePex device between August 2013 and January 2014 at a VMMC centre in Harare. Endpoints are number and grade of adverse events associated with device circumcision, time to complete wound healing, client satisfaction with the procedure, and outcome. Results: The rate of medical ineligibility among adolescent males was high; 237/402 (35.9%) of study participants had to be excluded based on medical reasons. The severe/moderate adverse event rate was low at 2/402 (0.5%). No device displacements/self-removals were observed. Time to complete wound healing was shorter than in adults; 367/398 (92.2%) adolescents had completed wound healing by day 35, whereas 90% of adults had completed wound healing by day 56 as demonstrated in previous studies. Overall, adolescents were highly satisfied with the results of their circumcision. Conclusions: The study demonstrates that the PrePex device can be safely used in adolescents aged 13–17 years. The significant proportion of males opting for surgical circumcision and the high medical ineligibility suggest that surgical circumcision needs to be provided alongside PrePex services in programs targeting young age groups.